Estudo das propriedades ópticas de filmes finos e poços quânticos de GaAsPN/GaPN - Covre, Felipe Soares (2016)
Diluted nitride III-V semiconductor leagues have physical properties that make them interesting for applications on optoelectronic devices. The possibility to lattice matching GaAsPN with silicon makes this semiconductor interesting for studies. In this dissertation we investigated the optical and magneto optical properties of semiconductors nanostructures of the type GaP(N)/GaAsPN. Mesures of photoluminescence (PL), photoluminescence excitation (PLE) and magneto photoluminescence (Magneto-PL) under high fields (B≤ 15T) were performed in films of GaAsPN and multiple quantum wells (MQW) of GaAsPN/GaPN. We have studied localizations effects with measures of diamagnetic shift, stoke shift and the dependence of photoluminescence peak with temperature. We observed a negative diamagnetic shift for some samples, which is an anomalous effect in these systems. It was also seen a red shift of the PL peak when the MQW samples suffered a thermal treatment. Analyzing the spin polarization properties of this material, utilizing magneto photoluminescence resolved with circular polarization, we observed polarization of the samples as high as 30% on fields of 15T.